2016
DOI: 10.1038/srep35460
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparison between quercetin and quercetin 3-O-β-glucuronide in rats by UHPLC-MS/MS

Abstract: Quercetin is a natural flavonoid widely distributed in human diet and functional foods. Quercetin 3-O-β-glucuronide (Q3G) is present in wine and some medicinal plants. Quercetin and Q3G may be metabolized from each other in vivo. While quercetin has been the subject of many studies, the pharmacokinetic profiles of quercetin and Q3G (in animals) have not yet been compared. Herein, we prepared a column-based method for rapid isolation of Q3G from Nelumbo nucifera. Then, we developed an UHPLC-MS/MS method to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
7
48
0
Order By: Relevance
“…Quercetin is a widely used dietary flavonoid, which can be directly absorbed into epithelial cells in the intestine to enter the circulatory system finally. Therefore, it can be more easily and faster absorbed in plasma with t max of 0.1 h. The pharmacokinetic profile of liquiritin was similar to a previous report [ 31 , 32 ]. Liquiritin and senkyunolide I were rapidly absorbed and eliminated after oral administration.…”
Section: Resultssupporting
confidence: 87%
“…Quercetin is a widely used dietary flavonoid, which can be directly absorbed into epithelial cells in the intestine to enter the circulatory system finally. Therefore, it can be more easily and faster absorbed in plasma with t max of 0.1 h. The pharmacokinetic profile of liquiritin was similar to a previous report [ 31 , 32 ]. Liquiritin and senkyunolide I were rapidly absorbed and eliminated after oral administration.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, in this study, Q3G suppressed the gene expression of atrogin-1 and MuRF1 and phosphorylation of AMPK in DEX-treated C2C12 cells, as well as up-regulated phosphorylation of mTOR and AKT ( Figure 6 D–G). Furthermore, a pharmacokinetic comparison study revealed that the area under the curve (AUC) of Q3G was 18-fold higher than that of quercetin in rat plasma after oral administration, indicating that Q3G was superior to quercetin in terms of absorption rate [ 52 ]. Based on these previous reports and our results, we predict that Q3G is the active component in LL for alleviating DEX-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hepatic glucuronidation of flavonoids, such as quercetin, naringenin, or hesperetin is known to be one of the most important metabolic pathways, and glucuronides are often the predominant flavonoid forms found in blood or urine [ 32 , 33 ]. The glucuronide metabolites could serve as the reservoir for bioactive aglycones through enterohepatic circulation, resulting in an increased half-life and prolonged pharmacological effects in vivo [ 34 , 35 , 36 ]. Thus, it can be speculated that glucuronidation of both SKN and its phase I metabolite, naringenin, as demonstrated in the present study, plays a role in the pharmacodynamic and pharmacokinetic behaviors of orally consumed SKN, although further research is required to probe the fate of SKN and its phase I and phase II metabolites in preclinical models.…”
Section: Discussionmentioning
confidence: 99%